USE OF ONLINE APPLICATIONS DURING THE COVID-19 PANDEMIC BY ADULT STUDENTS AT COMMUNITY LEARNING CENTERS - Budi Santoso; Ahmad Hufad; Uyu Wahyudin; Asep Saepudin; Purnomo Purnomo (IKIP Siliwangi Bandung, 2023)
Implementation of learning at the Community Learning Center (PKBM) during the Covid 19 pandemic faced challenges, this was due to the diversity of backgrounds of students in PKBM. The majority of students in PKBM are adults, due to the nature of PKBM which is flexible and oriented to community needs. The use of applications in learning during a pandemic is an option that must be used. However, adults who were born as digital immigrants need to adapt to this new technology. This research was carried out by applying a quantitative approach, using a survey method, namely research examining large and small populations (universe) by selecting and studying selected samples from that population, so as to find the relative incidence, distribution, and interrelation of variables and located in the city Bandung. Data collection through observation, interviews, documentation studies, and questionnaires. The population of this study amounted to 77 PKBM institutions, obtained a sample with the slovin formula totaling 43 PKBM institutions, with a total of 200 PKBM students representing each institution. The results of the study show that the most widely used learning media is WhatsApp, The use of the whatsapp application is more applicable and familiar how to use it.